Waiting for the BiblioBurro - Brown, Monica, 1969- (Tricycle Press, 2011)
When a man brings to a remote village two burros, Alfa and Beto, loaded with books the children can borrow, Ana's excitement leads her to write a book of her own as she waits for the BibliBurro to return. Includes glossary of Spanish terms and a note on the true story of Columbia's BiblioBurro and mobile libraries in other countries.